Multipotent Adult Progenitor Cells Enhance Recovery After Stroke by Modulating the Immune Response from the Spleen. (6th March 2017) - Yang, Bing; Hamilton, Jason A.; Valenzuela, Krystal S.; Bogaerts, Annelies; Xi, XiaoPei; Aronowski, Jaroslaw; Mays, Robert W.; Savitz, Sean I.
Abstract : Stem cell therapy modulates not only the local microenvironment of the brain but also the systemic immune responses. We explored the impact of human multipotent adult progenitor cells (MAPC) modulating splenic activation and peripheral immune responses after ischemic stroke. Hundred twenty-six Long-Evans adult male rats underwent middle cerebral artery occlusion. Twenty-four hours later, they received IV MAPC or saline treatment. At 3 days after infusion, RNA was isolated from the injured cortex and spleen for microarray analysis. Spleen mass, splenocyte phenotype, and releasing cytokines were measured. Serum cytokines, MAPC biodistribution, brain lesion sizes and neurofunctional deficits were compared in rats treated with MAPC or saline with and without spleens. Stroked animals treated with MAPC exhibited genes that more closely resembled animals with sham surgery. Gene categories downregulated by MAPC included leukocyte activation, antigen presentation, and immune effector processing, associated with the signaling pathways regulated by TNF-α, IL-1β, IL-6, and IFN-γ within the brain. MAPC treatment restored spleen mass reduction caused by stroke, elevated Treg cells within the spleen, increased IL-10 and decreased IL-1β released by splenocytes. MAPC reduced IL-6 and IL-1β and upregulated IL-10 serum levels. Compared with saline, MAPC enhance stroke recovery in rats with intact spleens but had no effects in rats without spleens. MAPC restores expression of multiple genes and pathways involved in immune and inflammatory responses after stroke. Immunomodulation of the splenic response by the intravenous administration of MAPC may create a more favorable environment for brain repair after stroke.